This house is haunted ebook A novel by the author of the heart's invisible furies. - Boyne, John (2013)
A Dickensian ghost story from the bestselling author of The Heart’s Invisible Furies and A Ladder to the Sky “A wonderfully creepy novel…magnificently eerie.” — The Observer This House Is Haunted is a striking homage to the classic nineteenth-century ghost story. Set in Norfolk in 1867, Eliza Caine responds to an ad for a governess position at Gaudlin Hall. When she arrives at the hall, shaken by an unsettling disturbance that occurred during her travels, she is greeted by the two children now in her care, Isabella and Eustace. There is no adult present to represent her mysterious employer, and the children offer no explanation. Later that night in her room, another terrifying experience further reinforces the sense that something is very wrong.   From the moment Eliza rises the following morning, her every step seems dogged by a malign presence that lives within Gaudlin’s walls. Eliza realizes that if she and the children are to survive its violent attentions, she must first uncover the hall’s long-buried secrets and confront the demons of its past. Clever, captivating, and witty, This House Is Haunted is pure entertainment with a catch.